Application of the Hungarian Method for Assigning Workers to Ciptaland Development - Wosvo Aritonang; Nelly Astuti Hasibuan; Rivalri Kristianto Hondro (The IJICS (International Journal of Informatics and Computer Science), 2020)
Assignment of workers is something that is needed by the company. But in reality the company is difficult to place its employees in each allocation. However, with the development of existing technology, this can be minimized by calculating the cost of each work and each allocation by utilizing existing data and extraction to produce new knowledge. The application of operational research techniques using the Hungarian method and tested using a system or application as a decision tree to assign some decent workers to be placed on jobs within the company. Therefore the author took the initiative to make a thesis entitled "Application of the Hungarian Method in Assigning Ciptaland Development Workers". The assignment process can show every worker by the company. So that Ciptaland Development can be a reference in making decisions in assigning and allocating workers. In this study, an Assignment model was made to determine the allocation of workers who were fit to be placed. This method is quite efficient in the allocation of workers. In applying this hungarian method can provide solutions or considerations for companies in making decisions